Pharmacology and metabolomic reveal Polysaccharides from polygonatum sibiricum ameliorate the diabetic osteoporosis in zebrafish - Ziping Chen; Na Li; Zhou Zhou; Lin Zhu; Kai Wang; Shijin Chen; Quan Gu; Yujun Liu; Kefeng Zhai; Shuwen Xu (BMC Complementary Medicine and Therapies)
Abstract Background Previous studies found that Polygonatum sibiricum polysaccharide (PSP) exhibited anti-inflammatory and anti-oxidative effects on type 2 diabetes (T2DM). However, the roles and detailed mechanisms of PSP on the anti-diabetic osteoporosis are still poorly defined. The purpose of this study was to identify the detailed mechanisms of PSP-induced anti-diabetic osteoporosis. Methods The roles of PSP on diabetic osteoporosis were evaluated on a T2DM zebrafish model. Furthermore, the changes of related physiological indicators and metabolites in adult zebrafish (Danio rerio) were investigated by pharmacology and metabolomic analyses. Results Results showed that PSP significantly reduced the blood glucose content and induced caudal fin regeneration. Metabolomic analysis found that the key metabolites involved in arachidonic acid metabolism, PPAR signaling pathway, linoleic acid metabolism, steroid hormone biosynthesis, amino acid biosynthesis and metabolism, alpha-Linolenic acid metabolism, sphingolipid signaling pathway were affected by PSP treatment. Among these, PSP reversed the trend changes of several metabolites, such as L-aspartic acid, choline, and propionylcarnitine. Besides, further changes of TNF-α and IL-1β transcripts suggested that the proinflammatory cytokines were also involved in the PSP-triggered anti-diabetic osteoporosis. Conclusion Above findings provided the theoretical basis for the use to plant PSP as food ingredients or bioactive compounds in natural health products on diabetic osteoporosis.